(3eONd Ydej eJcGed dEOGQI GdJShjb GdOhdj hGdYGdejs - (3eMeO SQhQ(B, (3GdMQjQjs ((3YeGf(B:s (3OGQ UaGAddfTQ hGdJhRjY(B,s, 2012)
(3eONd YGe dEOGQI GdJShjb GdOhdj hGdYGdej (B- (3ESJQGJjLjGJ GdJShjb GdOhdj hGdYGdej GdeYGUQ GdMOjK (B- (3GdESJQGJjLjGJ GdMOjKI aj efXeGJ GdJShjb GdOhdjIs
Keywords: (3EOGQI GdeHjYGJs; (3GdJShjbs; (3GdJShjb GdOhdjs